Minat Karir Siswa di Bidang Sains: Studi Pembelajaran Berbasis STEM pada Topik Buffer - Mabrukah, Nabilah Putri; Wiyarsi, Antuni; Kamari, Azlan (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2025)
The modern era is currently highly dependent on technology in almost all aspects, so the demand for experts in the field of technology is increasing. However, this does not match the situation in schools. Therefore, countries in the world are starting to implement the STEM approach to the national curriculum. This study aims to determine the increased interest in a career in science for students after applying the STEM approach. This research is a quasi-experimental using pretest-post-test control group design. The instrument used scientific career interest questionnaire that refers to the Social Cognitive Career Theory. The results show that the application of STEM through STEM activities such as formulating problems, designing solutions, practicums, and planning projects, will provide knowledge about students' career interests. The increase in students' career interest in science in the material on buffer solutions shows significant results. Environmental aspects more dominantly influence students' career interests with the dominant indicator being school teaching staff. Further research can be carried out to see the increase in students' interest in careers in science after implementing a STEM approach at a larger sample level such as a sample of high school students in a city.